Balancing the evidence: An update on analgesic use in rheumatic and musculoskeletal diseases - Huang, Yun-Ting; McCarthy, Craig; Jani, Meghna (Frontiers in Drug Safety and Regulation, 2023)
Pain management has been a challenging issue for people living with rheumatic and musculoskeletal diseases (RMDs) and health professionals for decades. Pharmacological treatments remain a core element of pain management of inflammatory arthritis and osteoarthritis. Yet balancing the benefits/ harms in pain management within RMDs can be difficult to navigate due to limited effective options, and emerging adverse events in a population where individual risk is important to consider due to patient multimorbidity, immunosuppression and polypharmacy. Paracetamol and non-steroidal anti-inflammatory drugs (NSAIDs) analgesics are widely used among RMD patients, however both classes of drugs have been associated with new safety concerns in the last two decades. Perhaps as a result in combination with multifactorial influences, opioid prescribing has increased from the 2000s to 2010s in the majority of RMD focussed studies, accompanied with a rising trend of long-term opioid use, despite limited evidence on efficacy. Gabapentinoids have also shown increasing trends more recently, despite an unclear role in chronic pain management for RMDs within current guidelines. Antidepressants are recommended as the first line of pharmacological treatment of chronic primary pain (e.g. fibromyalgia) by the latest National Institute for Health and Care Excellence guideline released in April 2021. This review will discuss pharmacological options for pain management, based on the latest evidence that includes the main analgesic drug classes: paracetamol, NSAIDs, opioids, antidepressants, and gabapentinoids. We will discuss the efficacy of these analgesics in RMDs and emerging safety concerns to enable more informed shared decisions with patients commencing such medications.